Cryptanalytic attacks on Rivest, Shamir, and Adleman (RSA) cryptosystem: issues and challenges - Abubakar, Adamu; Jabaka, Shehu; Tijani, Bello Idrith; Zeki, Akram M.; Chiroma, Haruna; Usman, Mohammed Joda; Raji, Shakirat; Mahmud, Murni (Little Lion Scientific Islamabad Pakistan, 2014)
RSA cryptosystem is an information security algorithm used for encrypting and decrypting of digital data in order to protect the content of the data and to ensure its privacy. Prior research studies have shown that RSA algorithm is very successful in protecting enterprises commercial services and systems as well as web servers and browsers to secure web traffic. In an email application, it's utilized to ensure the privacy and authenticity of email message. Some studies have also shown the efficiency of RSA algorithm in securing remote login sessions, and electronic credit-card payment systems. Generally RSA algorithm gain a security support because of it’s frequently use in most applications where security of digital data is mostly a concern. Its strength lies with its ability of withstanding many forms of attacks. While many studies focus on proving that RSA algorithm is breakable under certain cryptanalytic attacks, yet there are some confrontations on the circumstances of applying those attacks. This paper presents the issues and challenges on some key aspects of cryptanalytic attacks on RSA algorithm. The paper also explores the perceived vulnerabilities of implementing RSA algorithm which can render a cryptanalyst easier means of attack.